Development of a Web-Based Student Grade Information System as a System for Processing Student Grades and Monitoring Student Progress at SMK Negeri 1 Mondokan - Sari, Ananda Mutiara; Setiawan, Arif (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2024)
Implementing a website-based information system as a system for processing student grades is a way to facilitate monitoring of student progress. Monitoring activities have a very important role for teachers, students, and parents/guardians. By implementing website-based student assessments, the system for processing student grades is recorded manually using spreadsheets. This research uses research and development methods through the application of four method stages, namely exploration, development, testing, and dissemination. The results of implementing a website-based information system as a student grade processing system aim to create a website-based assessment system, a precise and accurate student grade processing system. The research results show that the use of a website-based student assessment system can speed up the teacher's work in monitoring student development. Apart from that, it can make it easier for parents to monitor their students at school. The use of a website-based assessment system has proven effective in monitoring student progress. Therefore, it can be concluded that a website-based assessment system can be a useful system in the world of education, especially for monitoring student progress in schoolBahasa IndonesiaPenerapan sistem informasi berbasis website sebagai sistem pengolahan nilai siswa merupakan cara untuk memudahkan monitoring perkembangan siswa. Kegiatan monitoring mempunyai peranan yang sangat penting bagi guru, siswa dan orang tua/wali. Dengan diterapkan penilaian siswa berbasis website maka sistem pengolahan nilai siswa tercatat secara manual dengan spreadsheets. Penelitian ini menggunakan metode penelitian dan pengembangan (Research dan Development) melalui penerapan empat tahap metode yaitu eksplorasi, pengembangan, pengujian dan desiminasi. Hasil penerapan sistem informasi berbasis website sebagai sistem pengolahan nilai siswa bertujuan untuk menciptakan sistem penilaian berbasis website sistem pengolahan nilai siswa yang tepat dan akurat. Hasil penelitian menunjukkan bahwa penggunaan sistem penilaian siswa berbasis website dapat mempercepat pekerjaan guru dalam melihat perkembangan siswa. Selain itu, dapat mempermudah orang tua untuk monitoring anak didik mereka di sekolah. Penggunaan sistem penilaian berbasis website terbukti efektif dalam memonitoring perkembangan siswa. Oleh karena itu, dapat disimpulkan bahwa sistem penilaian berbasis website dapat menjadi sistem yang berguna dalam dunia pendidikan, khususnya untuk memonitoring perkembangansiswa di sekolah.